Synthesis of Binuclear Complexes of Cu (II), Ni (II) and Cr (III) Metal Ions Derived from Di-Imine Compound as Biterminal Binding Site Ligand - Ismaiel Mahjoub Muslah, Safa; J. Alabdali, Ammar; D. Shaalan, Nasser (Al-Nahrain Journal of Science, 2020)
The research is concerning synthesis of two di-imine ligands derived from thiadiazole heterocyclic compounds. 1, 3, 4-thiadiazole-2, 5-dihydrazino is considered as ligand (L1) and starting essential compound that used as precursor to synthesize the new ligand (2, 2'-(((1,3,4-thiadiazole-2,5-diyl)bis(hydrazin-2yl1ylidene))bis (methaneylylide)) diphenol (L2). Six new complexes were derived from the ligands using some transition metal ions like Cu(II), Ni(II), and Cr(III).The synthesized compounds characterized by infra-red, ultra-violet-visible and gas chromatography-mass spectroscopy, conductivity, and thermal analysis. The coordination modes were suggested to be N2 from two terminals to form binuclear complexes.The mentioned characterization methods showed that the prepared complexes may have chelation pattern (bidentate or tridentate) depending on the suggested geometry (square planer or octahedral) and the type of ligand.